PERSEPSI NELAYAN TERHADAP DAMPAK PERUBAHAN IKLIM PADA SUMBER DAYA PERIKANAN DI KECAMATAN SUNGAILIAT BANGKA - Ainin, Dewi Tumatul; Khasanah, Nur; Muharani, Laily; Alfaresyah, Priestian; Handayani, Fitri (Universitas Garut, 2025)
Climate change has had a significant impact on the fisheries sector, especially in coastal areas that depend on marine resources. This study aims to identify and analyze fishermen’s perceptions in Sungailiat District, Bangka Regency, regarding the impact of climate change on their fisheries resources. The research employed a qualitative approach using in-depth interviews, focus group discussions (FGD), and field observations. The findings indicate that fishermen are aware of changing weather patterns, rising sea temperatures, and shifts in ocean currents that affect their catch and safety at sea. Some adaptations made by fishermen include changes in fishing techniques, adjusting their fishing times, and improving fishing gear. However, limited resources and knowledge about long-term adaptation strategies remain challenges for these fishermen. This study recommends enhancing education and providing policy support for climate change adaptation to better prepare fishermen for increasingly unpredictable environmental changes. Keywords: adaptation, climate change, fishermen’s perceptions, fisheries, Sungailiat